Explaining the Sub-National Tax-Grants Balance in OECD Countries - Charbit, Claire (OECD Working Papers on Fiscal Federalism, 2010)
Normative principles provide a relatively clear set of rules for the balance between grants and taxes (box 1 reviews the normative theory), but in practice a variety of types of tax-grant systems are observed in OECD countries, which do not all follow these rules. According to the theory, own-taxes should be the primary revenue source (technically for the last dollar of spending), while transfers should only be used as a supplementary revenue source to correct for externalities, act as an insurance buffer, or redistribute resources between regions (see OECD 2006a, 2006b). Besides, the theory wants tax bases for sub-national governments to be confined to immobile resources such as land and user fees. In practice, transfers often represent a large proportion of sub-national governments' revenues, and many countries use income taxes instead of property taxes at the sub-national level